Anxiety, Anxiety Sensitivity, and Perceived Stress as Predictors of Recent Drinking, Alcohol Craving, and Social Stress Response in Heavy Drinkers - McCaul, Mary E.; Hutton, Heidi E.; Stephens, Mary Ann C.; Xu, Xiaoqiang; Wand, Gary S. (Alcoholism, clinical and experimental research, 2017)
Background Stress and anxiety are widely considered to be causally related to alcohol craving and consumption, as well as development and maintenance of alcohol use disorder (AUD). However, numerous preclinical and human studies examining effects of stress or anxiety on alcohol use and alcohol‐related problems have been equivocal. This study examined relationships between scores on self‐report anxiety, anxiety sensitivity, and stress measures and frequency and intensity of recent drinking, alcohol craving during early withdrawal, as well as laboratory measures of alcohol craving and stress reactivity among heavy drinkers with AUD. Methods Media‐recruited, heavy drinkers with AUD (N = 87) were assessed for recent alcohol consumption. Anxiety and stress levels were characterized using paper‐and‐pencil measures, including the Beck Anxiety Inventory (BAI), the Anxiety Sensitivity Index‐3 (ASI‐3), and the Perceived Stress Scale (PSS). Eligible subjects (N = 30) underwent alcohol abstinence on the Clinical Research Unit; twice daily measures of alcohol craving were collected. On day 4, subjects participated in the Trier Social Stress Test; measures of cortisol and alcohol craving were collected. Results In multivariate analyses, higher BAI scores were associated with lower drinking frequency and reduced drinks/drinking day; in contrast, higher ASI‐3 scores were associated with higher drinking frequency. BAI anxiety symptom and ASI‐3 scores also were positively related to Alcohol Use Disorders Identification Test total scores and AUD symptom and problem subscale measures. Higher BAI and ASI‐3 scores but not PSS scores were related to greater self‐reported alcohol craving during early alcohol abstinence. Finally, BAI scores were positively related to laboratory stress‐induced cortisol and alcohol craving. In contrast, the PSS showed no relationship with most measures of alcohol craving or stress reactivity. Conclusions Overall, clinically oriented measures of anxiety compared with perceived stress were more strongly associated with a variety of alcohol‐related measures in current heavy drinkers with AUD. Stress and anxiety are widely believed to contribute to drinking; however, prior research findings have been inconsistent. In this study, measures of anxiety and anxiety sensitivity as compared with perceived stress were more strongly associated with frequency and intensity of drinking, alcohol craving during withdrawal, and alcohol craving and cortisol levels following the Trier Social Stress Test. These findings highlight the importance of maintaining distinctions among these terms given unique relationships with drinking, craving, and stress reactivity among heavy drinkers.